Emerging role of ultrasound guided interventional management in cervicogenic headache - Sarah Razaq; Sajjad Ali Akbar; Zahid Rustam; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
The objective of this mini review is to discuss the role of musculoskeletal ultrasound (MSK US) in identification and treatment of pain generators in cervical spine in patients presenting with cervicogenic headache (CEH). CEH is a secondary headache arising from cervical nociceptive structures emerging from facet joints, intervertebral discs, nerves, muscles, fascia and ligaments. It presents a complex challenge in clinical management. Traditional treatments often provide limited relief, prompting the exploration of innovative interventions like US guided techniques. MSK US is gaining momentum since last 2 decades and it has transformed the interventional management options for diverse conditions including CEH with improved accuracy and efficacy. The management of CEH needs to be multidisciplinary keeping biopsychosocial model of pain in mind. In countries like Pakistan, there is a huge potential to apply US guided procedures in its population, as it reduces the number of visits by the patient and reduces the overall healthcare cost. By targetting specific pain generators and minimizing collateral damage, these interventions hold immense promise in improving the management. Herein, we briefly discuss the diagnosis of CEH and evidence based US guided interventions on cervical pain generators.